2004
DOI: 10.1300/j073v17n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Buyer Characteristics Among Users of Various Travel Intermediaries

Abstract: As online travel purchases increase, travel intermediaries must change to meet consumer demands. A survey was conducted to identify travelers' selection criteria and expectations of traditional travel agents. Responses from 382 individuals were compared by their methods of purchasing travel arrangements, including those who purchased online, offline, or both. Differences were found among the groups in terms of travel agent selection criteria and expectations; however, the groups were similar in their frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…In fact, in Morrison et al's model (2001), education was found to be the only sociodemographic variable that affected the likelihood of using the Internet to purchase travel. Yet, other studies found that there was no relationship between them (Beldona, Racherla, & Mundhra, 2011;Garín-Muñoz & Pérez-Amaral, 2011;Li & Buhalis, 2006;Wolfe et al, 2004). Strangely, Chen (2006) found that consumers with higher education levels did not trust travel websites as much.…”
Section: Demographic Variablesmentioning
confidence: 95%
See 4 more Smart Citations
“…In fact, in Morrison et al's model (2001), education was found to be the only sociodemographic variable that affected the likelihood of using the Internet to purchase travel. Yet, other studies found that there was no relationship between them (Beldona, Racherla, & Mundhra, 2011;Garín-Muñoz & Pérez-Amaral, 2011;Li & Buhalis, 2006;Wolfe et al, 2004). Strangely, Chen (2006) found that consumers with higher education levels did not trust travel websites as much.…”
Section: Demographic Variablesmentioning
confidence: 95%
“…However, individuals between the ages of 25 to 55, possessing higher levels of education and income, were more likely to purchase travel online. Effectively, the majority of the succeeding studies also found that travelers with higher education levels were more likely to purchase travel online (Heung, 2003;Kamarulzaman, 2007Kamarulzaman, , 2010Kim & Kim, 2004;Law, Leung, & Wong, 2004;Lee, Qu, & Kim, 2007;Li & Buhalis, 2006;Morrison, Jing, O'Leary, & Cai, 2001;Wolfe, Hsu, & Kang, 2004), but not without some contradictory evidence (e.g., Weber & Roehl, 1999). In fact, in Morrison et al's model (2001), education was found to be the only sociodemographic variable that affected the likelihood of using the Internet to purchase travel.…”
Section: Demographic Variablesmentioning
confidence: 97%
See 3 more Smart Citations